Ragam Rangkaian Bunga sebagai Penghias Lobby Hotel di Kawasan Wisata Ubud, Bali - Ida Ayu Sri Puspa Adi (JURNAL BISNIS HOSPITALITI, 2023)
The hotel lobby is the first area that a guest enters, so it is important to make a good first impression. One way to do this is to put some flower arrangement. Therefore, this study aims to identify the characteristics of flower arrangements used as decorations in hotel lobbies in the Ubud in terms of: the basic shape of the arrangement, the placement of the flower arrangement, the type of flower used, the container/vase used in the flower arrangement, the durability of the flower, and the color of the flower. The data were obtained through interviews with the hotel staff who determine the procurement of lobby interest and through observation. The results showed that the variations in the basic shape of the flower arrangement used, the placement varied from as a center piece to the reception desk, the types of flowers picked in the hotel garden, tropics, commonly used cut flowers and orchids, the resistance was different, as well as the colors used are various colors